MANAJEMEN PENDIDIKAN ISLAM PADA LEMBAGA PAUD - Rina Insani Setyowati; Arif Muzayin Shofwan; Hendrik Setyowati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study, entitled “Islamic Education Management in Early Childhood Education Institutions (PAUD)”, aims to analyze and describe the implementation of Islamic education management in Early Childhood Education institutions, particularly in terms of planning, implementation, and evaluation of learning programs grounded in Islamic values. The specific objectives of this research are to identify Islamic managerial practices applied in PAUD institutions, to document the challenges and constraints encountered in their implementation, and to formulate strategic recommendations for optimizing Islamic education management in PAUD. This study employs a descriptive qualitative approach, with data collected through observation, in-depth interviews, and documentation involving principals, teachers, and administrators of Islamic PAUD institutions. The research procedures include a preparation stage (instrument development), data collection, data analysis using the Miles and Huberman model, and the compilation of the research report. The expected outcomes of this study are the production of a research report that may serve as a reference for the development of Islamic education management in PAUD, the formulation of policy recommendation documents for institutional managers, and the publication of a scientific article in a nationally accredited journal as a means of disseminating the research findings. This study is expected to make a substantive contribution to strengthening the quality of governance in Islamic-based PAUD institutions in fostering children’s character and moral development from an early age